The Contribution of Hand-Eye Coordination, Muscle Arm Strength, and Concentration to Standing Throw Shoot Results (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
The purpose of this research is to: (1) Analyze the contribution of eye-hand coordination to the result of standing throw shoot; (2) Analyzing the contribution of arm muscle strength to the result of standing throw shoot; (3) Analyzing contribution of concentration to result of standing throw shoot; (4) Analyze the contribution of eye-hand coordination, arm muscle strength, and concentration to the result of standing throw shoot. This study uses correlation analysis. The research procedure is: (1) preliminary study, (2) determining the variable, (3) making the research instrument, (4) taking the data, (5) processing the data. The subjects of this study were students of SMP Negeri in Semarang City who followed extracurricular handball which amounted to 70 students. Instruments and techniques of data collection using tests. Data analysis used simple regression and multiple regression analysis. The results showed that hand-eye coordination contributed 23.4%, arm muscle strength contributed 15.8%, concentration contributed 19%, and hand-eye coordination, arm muscle strength, and concentration together contributed significantly by 54.2%. The conclusion of this research is the factor of hand-eye coordination, arm muscle strength, concentration has a contribution to the result of standing throw shoot either alone or together.